Legal Problems Concerning the Local Finance: Case Study Udon Thani Province - Lortrakul, Suttichai (Interdisciplinary Academic and Research Journal, 2023)
Local treasury is an important component of public finance or national treasury. Local finance is part of the decentralization of governance and administration between the central government and local governments. It is the delegation of fiscal authority and responsibility to the local government. This article, therefore, aims to study the problems of local treasury management, which are related to the government, the relationship and conflict between local governments and central authorities, and local fiscal problems that have been submitted. impact on people in the area. The article is a combination method. Use document synthesis, questionnaires, and in-depth interviews. The study found that Local fiscal management problems are divided as follows; 1) Local fiscal management problems related to the "government". 2) Relationship problems and conflicts between local government organizations and central agencies. 3) Local fiscal management problems related to "Local government organization". And 4) Fiscal management problems related to “people”. As for the problem of local fiscal administration of local government organizations in Udon Thani Province moderate Most of the income problems, followed by expenditure and public debt, comparing the problems according to the type of local government organization with the income size of various local government organizations found that there was no difference When considering the income, it was found that there was no difference as well, and guidelines for the development of local fiscal administration to raise public service levels of local government organizations. Guidelines for the development of local fiscal management in terms of income, expenditure, regulations, and laws related to state audits of local government organizations. Therefore, it can be concluded that the fiscal problem There are principles to study the expenditure management of Udon Thani Municipality, budget, planning, revenue management, conditions, limitations, or general fiscal problems to assess the fiscal potential in budget management whether there is potential or not and the opportunity for development. What makes it more efficient, emphasizes the efficiency of revenue management, and the efficiency of expenditure management.